Current Issues of Legal Regulation of Mentoring in Healthcare - N. L. Arakelyan; E. S. Vorobtsova (Здоровье мегаполиса)
Purpose. The article discusses the latest changes in the labor legislation of the Russian Federation regarding the mentoring system, particularly, in healthcare. In response to the President's instruction on tightening labor regulations related to mentoring dated July 25, 2023, a draft federal law was proposed, and further adopted on November 9, 2024. Materials and methods. The presented study analyzes the new federal law that amends the Labor Code of the Russian Federation in the field of mentoring. The article also analyzes important aspects of creation and regulation of a mentoring system, examines possible ways of mentor encouragement, and emphasizes the need for support from government authorities and educational institutions. Results. Based on the results obtained, it was concluded that the introduction of a mentoring system under the new legislation would ensure the sustainable development of skilled workforce, increase the level of medical care and improve the overall competitiveness of Russian healthcare in the modern labor market.